Analisis Perlindungan Konsumen Dalam Kaitannya Dengan Globalisasi Pasar Dunia - Primandiri, Handayani (UI Scholars Hub, 2022)
Globalization of the world market has created vast business opportunities and increased consumer access to international products and services, but it has also brought new complexities to consumer protection. This research analyses the relationship between consumer protection and world market globalization by examining its positive and negative impacts. On the one hand, globalization expands product choice and increases competition, which can benefit consumers. However, on the other hand, it also poses risks such as an increase in illegal trade, counterfeit products, and inequality in access to consumer information. The study also identifies the role of international and national institutions in protecting consumers in the era of globalization and compares consumer protection policies across countries to understand best practices that can enhance consumer protection amidst the changing globalization of the world market. This research provides a deeper understanding of the complex relationship between globalization and consumer protection, which can be used as a basis for the development of more effective policies to safeguard the rights and interests of consumers in an era of evolving globalization.